PEMBERDAYAAN POTENSI LOKAL BUAH SEMANGKA SEBAGAI PRODUK UMKM UNTUK MENINGKATKAN EKONOMI MASYARAKAT DESA SUKAMAKMUR, KECAMATAN TOLANGOHULA, KABUPATEN GORONTALO - Nuna, Muten; Tabo, Sarfan; Hunawa, Robby; Junus, Dikson; Podungge, Abdul Wahab; Sahi, Nirmala; Mahriadi, Nopriawan; Walahe, Dewi; Hasan, Silvana; Napir, Suaib; Harun, Nur Istiyan; Polinggapo, Jefri; Arsjad, Muh. Fachri; Paweni, Lisnawati; Bilondatu, Nikma; Biongan, Ahiar; Bahlun, Wanda; Sukarna, Yovin (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STISIPOL Candradimuka, 2025)
Community Service Program (Kuliah Kerja Pengabdian/KKP) is an implementation of the Tri Dharma of Higher Education focusing on community engagement. This program aims to empower students as agents of change through the application of knowledge in the field. This research was conducted in Sukamakmur Village, Tolangohula District, Gorontalo Regency, an area with abundant watermelon agricultural potential. The urgency of this research lies in the need to optimize watermelon processing to increase its economic value, foster awareness of clean and healthy living, and strengthen community cohesion. The KKP activities were carried out for 45 days, encompassing observation, interviews, discussions, and direct training. The demonstration method was employed in the training for processing watermelons into stick and jam products. Additionally, socialization on Clean and Healthy Living Behavior (PHBS), free health check-ups, and arts and sports activities were conducted. The results show that the community successfully understood and practiced watermelon processing into valuable products. There was an increase in community awareness regarding PHBS, and cohesion was fostered through social activities. The implications of these activities include the realization of economic empowerment, improved health, and strengthened social bonds within the community. For the sustainability of the program, continuous mentorship from the local government and universities is recommended to develop the processed watermelon business and enhance community participation in maintaining health and environmental cleanliness.